THE IMPACT OF INTERNATIONAL YOGA DAY WORLDWIDE - Dr.Rashmi Ranade, Dr.Jaydeep Nikam (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The global celebration of International Yoga Day has been marked with great enthusiasm since its inception in 2015. The initiative was proposed by the former and current Prime Minister of India, Hon.Mr. Narendra Modi, during a UN General Assembly’s meeting in September 2014, and was promptly accepted. Commencing on 21st June 2015, International Yoga Day was observed not only in India but also across the world, leading to a surge in the popularity and understanding of Yoga. The subsequent period of the COVID-19 pandemic further underscored the importance of Yoga, resulting in a heightened global interest in its practice. As a result, International Yoga Day began to be celebrated in more countries, with different themes being adopted each year. The accessibility of yoga protocols also contributed to its widespread adoption. This research paper aims to analyse the variations and commonalities in the celebration of International Yoga Day from 2015 to 2024.